2018
DOI: 10.1016/j.jfludis.2018.10.002
|View full text |Cite|
|
Sign up to set email alerts
|

The Satisfaction with Communication in Everyday Speaking Situations (SCESS) scale: An overarching outcome measure of treatment effect

Abstract: Highlights The Consolidated Standards of Reporting Trials (CONSORT) strongly suggests one primary outcome for clinical trials. That presents a roadblock to eventual meta-analysis of randomized trials for adults who stutter. We propose a simple and convenient outcome measure for clinical trials of stuttering treatment that spans behavioral and psychosocial factors that might impel clients to seek treatment  Reliability, content validity and construct validity of the SCESS were confirmed. We conclude that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
0
8
1
Order By: Relevance
“…It may be possible that diminished positive emotions and experiential avoidance are related to higher stuttering severity and lower satisfaction with communication among AWS. Karimi et al (2018) revealed that satisfaction with communication, stuttering severity, and emotional disturbances, including anxiety, are related to each other between individuals. However, it has been shown that stuttering and anxiety, potentially predicting satisfaction with communication, are variable depending on speaking contexts within individuals (Constantino et al, 2020;Constantino et al, 2016;Diehl et al, 2018).…”
Section: Stuttering and Emotion Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…It may be possible that diminished positive emotions and experiential avoidance are related to higher stuttering severity and lower satisfaction with communication among AWS. Karimi et al (2018) revealed that satisfaction with communication, stuttering severity, and emotional disturbances, including anxiety, are related to each other between individuals. However, it has been shown that stuttering and anxiety, potentially predicting satisfaction with communication, are variable depending on speaking contexts within individuals (Constantino et al, 2020;Constantino et al, 2016;Diehl et al, 2018).…”
Section: Stuttering and Emotion Regulationmentioning
confidence: 99%
“…In treatments of AWS, not only ameliorating stuttering severity but also improving quality of life or well-being is warranted. Stuttering is a speech disorder; therefore, quality of speaking communication seems to be one important aspect of quality of life or well-being in adults who stutter (AWS) (Karimi et al, 2018;Koedoot et al, 2011;Yaruss & Quesal, 2006).…”
Section: Satisfaction With Communication As An Outcome Measure In Stuttering Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Satisfaction with uency 27 Adapted from the Satisfaction with Communication in Everyday Speaking Situations Scale 27 and completed on the on-line database. Children rate "how happy are you with your speech at the moment?"…”
Section: Recruitment and Retention Ratesmentioning
confidence: 99%